La guerra come interazione e comunicazione: A partire da Clausewitz e Simmel - Guareschi, Massimiliano (Mediascapes journal, 2024)
Starting from Clausewitz’s On War, reinterpreted through the lens of Georg Simmel’s formal sociology, this article aims to develop a theoretical framework for analyzing war as an interactive and communicative dynamic. The debates on nuclear deterrence in the 1960s, alongside the events of the war in Ukraine and the conflict between Iran and Israel, serve as empirical references to test the applicability of the proposed approach.